“Потойбіччя” в уявленнях прадавніх українців - Яковлєва, О. (Народна творчість та етнографія, 2005)
In the article the evolution of Slavic pre-Christian ideas about death, paradise and the next world are examined. Different assessments of these ideas made by linguists, historians and specialists in ethnography are illustrated in the texts of Ukrainian keening published in the XIX century. Key words: mythological thinking, ritual, paradise, paganism of ancient Slavs, the next world.